A structure equation model among factors of teachers' technology integration practice and their TPCK. (August 2015) - Chuang, Hsueh-Hua; Weng, Chih-Yuan; Huang, Fu-Chen
Abstract: This study used a structural equation model to investigate the latent structure of teachers' technology integration practice and its relation to their technological pedagogical content knowledge (TPCK). We developed a validated survey comprised of 10 items for the TPCK construct informed by competences as proposed byAngeli and Valanides (2009, 2013), 6 items for the construct of technology integration with ICT tools (TI-ICT tools), 4 items for that of technology integration with social media (TI-Social media) and another 4 items for technology integration with graphic and dynamic visualizations (TI-Graphic and dynamic visualizations), respectively. The survey was then administered using stratified random sampling in a metropolitan area of southern Taiwan, and a total of 320 valid respondents were collected from elementary and secondary school teachers in January 2014. Further analysis based on structural equation modeling showed that teachers' technology integration practice with ICT tools (TI-ICT tools) maintained not only a direct link to TPCK scores but also an indirect association mediated by that with graphic and dynamic illustrations (TI-Graphic and dynamic visualizations). In addition, the association between TI-Social media and self-assessed TPCK turned out to be spurious after the level of TI-ICT tools was accounted for. Discussion of the results is also provided. Highlights: We used SEM to investigate teachers' technology integration practice and knowledge. TI-ICT tools alone had a direct link to TPCK. TI-ICT tools had an indirect association mediated by TI-Graphic and dynamic visualizations. The association between TI-Social media and TPCK seemed spurious.